(untitled) (Texas Journal of Medical Science, 2022)
The functional states of the masticatory muscles are interrelated with the general states of the muscular systems and the whole organism as a whole. An increase in muscle-strength contractions during pathological tooth abrasion violates the compensatory-protective abilities of the dental-maxillary system, while the functional balance is disturbed, phenomena and features of active bruxism appear, all this is a key mechanism for the development of pathology